INNOVATIVE APPROACHES TO THE FORMATION OF INTERNATIONAL COMMUNICATION POLICY OF AN ENTERPRISE IN CRISIS CONDITIONS - KHACHATRYAN, Valentyna; STRATIICHUK, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The functioning of each enterprise inextricably linked with the use of material, financial and other types of resources aimed at ensuring the economic well-being of the enterprise. The lion's share in the structure of the resource potential of each enterprise occupied by current assets that participate in operational activities, affect the liquidity, solvency, and financial stability of the enterprise. Current assets are the main operating resource of trade enterprises, which ensures uninterrupted activity and the effectiveness of the functioning of the enterprise as a whole. An important stage in the process of managing current assets of modern trading enterprises is the process of their financing, which based on the use of scientifically, based types of current asset financing policies and their adaptation to modern business conditions. The theoretical and methodological foundations of financing current assets are substantiated, the diversification of types of policies of financing current assets is expanded by dividing the moderate policy of financing current assets into moderate saving, moderate balanced and moderate cost-intensive, which consists in distinguishing long-term liabilities into equity and long-term liabilities. As a result, a methodology for choosing the type of policy for financing current assets of trade enterprises proposed. The indicators of which are the value of the coefficient of provision of the current activity of the own working capital, the size of the enterprise, which is determined by the level of income from the sale of products and the type of policy for the formation of current assets. The last criterion will make it possible to build sustainable relations of the policy of formation and financing of current assets, will ensure the complexity of the process of strategic management of current assets.
Keywords: current assets; equity; current liabilities; long-term liabilities; innovative approach; current assets financing policy